PENGEMBANGAN TPS3R PENDEKATAN PENTAHELIX BERBASIS EKOWISATA DI KABUPATEN SITUBONDO - Syamsudin, Moch.; Supi'i (Integrative Perspectives of Social and Science Journal, 2026)
The regional development process by the Situbondo Regency Government has resulted in the emergence of waste problems. The condition of waste increases significantly every day, which is not in line with good and proper management. The waste problem is not only a government intervention but requires collective contribution. The study used a systematic literature review (SLR) approach with qualitative descriptive analysis. The results show that the condition of the problem of developing TPS3R (Reduce, Reuse, Recycle waste management facilities) in Situbondo Regency with the Pentahelix approach as a long term plan is determined by the level of commitment given by both the government and the community. The main conditions that occur upstream are problems that must be resolved quickly. Waste sorting from the source to waste reduction behavior needs to be carried out with a regulatory approach and direct appeals. On the other hand, awareness of the dangers of unmanaged waste must be encouraged from the beginning through an ecotourism approach for early childhood and as a form of educational promotion of waste-friendly tourism.